A Multiyear Assessment of Irrigation Cooling Capacity in Agricultural and Urban Settings of Central Arizona. (27th May 2021) - Wang, Zhaocheng; Vivoni, Enrique R.; Bohn, Theodore J.; Wang, Zhi‐Hua
Abstract: Irrigation water use associated with agricultural activities and urban green spaces provides substantial cooling effects and ameliorates heat in central Arizona. In this arid and semiarid area, evaluating the effect of irrigation on land surface temperature (LST) for different types of land use can improve decision making related to water resources management. In this work, we improved the simulation of urban and agricultural irrigation in the Variable Infiltration Capacity model through remotely sensed vegetation and irrigation parameters applied at high spatiotemporal resolution. We then conducted a multiyear (2004–2013) assessment of simulated LST with respect to ground observations and remotely sensed products finding overall good agreement. Overall, results show that irrigation of about 2 mm/day is required to reduce average daily LST by 1°C across the region. Numerical experiments with the validated model also reveal that irrigation leads to LST reductions of higher magnitude and greater spatial variability in croplands than in urban areas. Furthermore, we found that the role of interannual variations in cropping practices is more critical than year‐to‐year differences in climatic conditions for the evaluation of irrigation cooling capacity. Thus, remotely sensed vegetation products can serve a valuable purpose in quantifying LST reductions and irrigation requirements to achieve a target of heat amelioration. Abstract : Research Impact Statement : Remotely‐sensed vegetation datasets are used in a high‐resolution land surface model evaluated with land surface temperature to assess the spatiotemporal variations of irrigation cooling capacity.